(untitled) (Revista de História da UEG (REVHIST), 2022)
The article aims to identify and recognize the representations and motivations for the recurrence of conjugal physical violence against women, according to data and information obtained from police reports registered at the Specialized Police Service for Women in Vitória - Holy Spirit. The temporal delimitation of the investigation refers to the period from 2004 to 2010. The different profiles of the victims show that there is a specific profile for most of them: women between 20 and 29 years old, brown, black, living in neighborhoods peripheral parts of the city of Vitória, having as occupation domestic activities. Through the sources, it was possible to verify that the economic dependence of the woman is one of the main reasons that generate her permanence in the marital relationship, in which she suffers from the recurrence of physical violence. Also, it was evidenced that in addition to economic issues, there are other factors that reinforce the permanence of women in this relationship, in this case, children, family relationships, fear, and the culture that constitutes it, for the most part, cultural values ​​were shaped by ways of the patriarchal system. Keywords: Culture. Recurrence of Violence. Gender. Women.